FAKTOR INTERNAL DAN FAKTOR EKSTERNAL YANG MEMPENGARUHI NON-PERFORMING LOAN DI BANK PEMERINTAH DAN BANK SWASTA JAWA TIMUR PERIODE 2008-2012 - Halim, Marissya (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2015)
Banking institutions, especially the Bank, currently so easily give consent to the demand for credit which submitted by a customer. Most of the agreement was not accompanied with the investigation and supervision in advance by the bank in charge of the task. This leads to increasing the percentage of Non-Performing Loan (NPL). For this study aims to determine whether the internal factors (CAR, LDR, RC) and external factors (INF, ER, PDRB) banks affect the percentage of Non-Performing Loans (NPL) in particular on the State Bank and the Private Bank in East Java, period 2008- 2012. This study uses the banks annual financial statements compiled by Bank Indonesia East Java branch of the four State Banks and the four largest Private Banks in Indonesia. Estimates of the data panel regression results show the influence of internal factors on the percentage of Non-Performing Loan (NPL).